Using Data Mining Approach for Student Satisfaction With Teaching Quality in High Vocation Education - Chen, Bailin; Liu, Yi; Zheng, Jinqiu (Frontiers in Psychology, 2022)
high vocation education is an important foundation for china to cultivate high teaching quality, technical and skilled talents. In the new era, the acceleration of the development of modern vocational education is put in a more prominent position. It is proposed that we should adhere to moral education, closely combine with the needs of technological change and industrial upgrading, constantly improve the quality of high vocational education teaching, and cultivate more technical and skilled talents with both political integrity and ability for the modernization construction. Under the background of social informatization, using artificial intelligent technology to solve these problems can play an important role for improving the teaching quality of high vocational education. This paper proposed data mining approach in promoting student satisfaction with the teaching quality of high vocational education. Design a questionnaire for students’ satisfaction with the teaching quality of basic entrepreneurship curriculum. Take the survey data of vocation education as an example and use mining technology analysis software to understand the current status of the teaching quality of basic entrepreneurship curriculum and find out the main factors affecting students' satisfaction with teaching quality. The results of this paper, can application in student management, education strategy, student education satisfaction and teaching quality in high vocation college education, and to improve teaching quality of fundamentals of entrepreneurship curriculum in high vocation education.